The power of silence in marriage: gender-based reading of John 4:1-11 - Mligo, Elia Shabani (Stellenbosch Theological Journal, 2020)
Silence speaks louder than verbal speech, penetrating deeper into the hearts of those to whom it is directed. Marriage, as any other institution, is often surrounded by moments of silence between couples, which leads to thoughtful suffering. Contextualizing the theory of Spiral of Silence of Noelle-Neumann in the Bena context in Tanzania, this article provides a reading of the text in the Gospel according to John to discern the way in which it enlightens the real life situations of the church in regard to the role of silence. The article argues that the silence of Jesus in the text, as was his silence in the passion narratives, is a form of expression of his urgency and the communication of his power against the public opinion. In this case, the reading intents to look at the implication of silence within the prism of gender with specific reference to emotional abuses exerted by the church to marginalized people.